European thought and culture, 1350-1992 - Sauter, Michael J., author.
1 online resource
Keywords: "This book explores the main currents of European thought between 1350 and 1992, which it approaches in two main ways; culture as produced by place and the progressive unmooring of thought from previously set religious and philosophical boundaries. Offering a comprehensive introduction to European thought that stretches from the late fourteenth to the late twentieth century, this is the perfect one-volume study for students of European intellectual history"--